DEFENSE STRATEGIES OF ADOLESCENTS WITH A HISTORY OF ABUSE - Alina COSTIN (International Journal of Social and Educational Innovation)
Evidence shows that both in the family environment and in the special protection system, adolescents report abuse or neglect. We aim to explore the defense strategies of adolescents who have suffered abuse or neglect. The psychodynamic concept of defense mechanisms is nowadays considered by professionals with various theoretical orientations to be of great importance in understanding human development and psychological functioning. More than half a century of empirical research has demonstrated the impact of defensive functioning on psychological well-being, personality organization, and treatment outcome. Given a glaring lack in the literature of empirical studies based on the concept of defense mechanisms and childhood abuse and neglect, the main purpose of this paper is to investigate the existence of relationships between childhood trauma and abuse and the development of defense mechanisms during adolescence. The results indicate associations between maladaptive defense mechanisms (neurotic and immature) with high levels of abuse and neglect, but also the emergence of highly adaptive defense patterns, such as affiliation, sublimation and anticipation. Also, a trend toward negative association was observed between physical and sexual abuse and neglect and most adaptive defense mechanisms.